MADRASAH HEAD COMMUNICATION; TRANSFORMATION TOWARDS MADRASAH MANAGEMENT EFFECTIVENESS - Rifa’i, M.; Muchyiddin, Achmad (Managere: Indonesian Journal of Educational Management, 2022)
This research is based on facts for academics curious about how to Communicate with the Head of the Madrasa; Transformation Towards Effectiveness of Madrasah Management. The goal is to realize the effectiveness of teacher performance and student learning and minimize organizational conflicts with the communication style they need to compete in international competitions, as well as to provide answers and help madrasas improve educational standards. The research used is descriptive qualitative research. Descriptive qualitative research, namely research conducted by Sugiono and Kuntjojo to study a practice unusually to learn new information that has never been known before. The study subjects included madrasah heads, teachers, parents, and students. The communication research of the head of the madrasa is emphasized in 3 forms interpersonal, group, and mass communication.